1999
DOI: 10.1051/forest:19990406
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient efficiency and resorption in Quercus pyrenaica oak coppices under different rainfall regimes of the Sierra de Gata mountains (central western Spain)

Abstract: -Nutrient uptake, nutrient resorption and nutrient use efficiency (NUE) were estimated in four Quercus pyrenaica oak coppices situated in the Sierra de Gata mountains (province of Salamanca, central-western Spain). The efficiency (NUE) with which a given nutrient is used depends on several factors. In the oak coppices studied, availability of P, Ca and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…It is noticeable that the decrease pattern of P concentration in CL leaf litter is not so clear, which may be in relation with the higher P concentration in mature leaves and leaf litter of CL. Ca concentration in CS leaves increases along leaf life span, due to the low mobility of this bio-element, leading to a maximum concentration at senescence, during the dry season (Simões et al 2008), as observed for tree species in Mediterranean areas Gallardo et al 1999;Santa Regina 2000).…”
Section: Annual Potential Return Of Bio-elementsmentioning
confidence: 89%
“…It is noticeable that the decrease pattern of P concentration in CL leaf litter is not so clear, which may be in relation with the higher P concentration in mature leaves and leaf litter of CL. Ca concentration in CS leaves increases along leaf life span, due to the low mobility of this bio-element, leading to a maximum concentration at senescence, during the dry season (Simões et al 2008), as observed for tree species in Mediterranean areas Gallardo et al 1999;Santa Regina 2000).…”
Section: Annual Potential Return Of Bio-elementsmentioning
confidence: 89%
“…En contraposición, el espinal tuvo valores de calcio en hojas maduras que oscilaron entre 11,8 y 26,2 mg g -1 (siendo máximos en A. caven y C. tala), siendo en hojas senescentes del mismo orden (11,3 y 25,1 mg g -1 ). Las concentraciones de magnesio registradas por León Peláez et al (2009) en hojas maduras se ubicaron en el límite inferior del intervalo definido para un amplio núme-ro de bosques tropicales de tierras altas (1,2-3,0 mg g -1 ), mientras que en hojas senescentes bajó a 0,6-1,0 mg g -1 , debido a pérdidas por lixiviación (Gallardo et al 1999); valores similares se han encontrado en el espinal. Consecuentemente, la razón calcio:magnesio en hojas maduras y en hojas senescentes resultaron más altas en el espinal que en bosques tropicales, sugiriendo un desequilibrio en la relación calcio:magnesio, con mayor absorción del calcio en detrimento del magnesio.…”
Section: Discussionunclassified
“…Los bajos valores de la retranslocación para nitróge-no, evidenciados en Rc 1 y Rc 2 , en las especies de fabáceas (cuadros 4 y 5) denotan la escasa resorción del nitrógeno. Una elevada concentración de nitrógeno en hojas senescentes supone una baja retranslocación e, indirectamente, un mayor aporte de nitrógeno al suelo con el desfronde (Martín et al 1996, Gallardo et al 1999. La menor retranslocación del nitrógeno en especies de fabáceas respecto a lo observado en celtidáceas, está indicando una gran potencialidad de fijar nitrógeno por parte de las primeras, lo cual denota efectivamente la fijación biológica por parte de bacterias simbiontes, e indirectamente implica un mayor retorno de nitrógeno al suelo, siendo esto último de gran valor en los bosques nativos del Espinal Mesopotámico cuyo uso es fundamentalmente silvopastoril (Casermeiro et al 2001).…”
Section: Discussionunclassified
“…47 kg N ha -1 (about 56% of the total N) in a stand of Quercus serrata (Migita et al, 2007) or 7-27 kg N ha -1 , 0.5-1.8 kg P ha -1 , and 1.8-5.3 kg K ha -1 in several coppices of Q. pyrenaica (Gallardo et al, 1999). Changes in the flux of resorbed nutrients are accompanied by symmetrical changes in the flux of nutrients returned to the soil with the fallen leaves.…”
Section: Significance Of Nutrient Resorption For Winter Deciduous Plamentioning
confidence: 99%